Propriedades de medida de instrumentos para avaliação de alterações sensório-motoras em indivíduos com dor lombar crônica e assintomáticos - Claudio, Ana Carolina de Jacomo (Universidade Federal de São Carlos, 2025)
Introduction: The literature suggests that alterations in cortical plasticity appear to be present in chronic low back pain (CLBP) and may result in sensorimotor alterations. Some assessment instruments can be used to assess these alterations, such as the Fremantle Back Awareness Questionnaire (FreBAQ), two-point discrimination test (TPD), laterality judgment (LRJT), and body image drawing (BID). However, it is recommended that their measurement properties be tested. Thus, the objective of this dissertation was to test the measurement properties of the FreBAQ questionnaire and sensorimotor tests. Methods: Two studies were conducted: 1) The sample consisted of 279 participants, 178 with CLBP and 101 asymptomatic controls for low back pain. The measurement properties were analyzed: structural validity, internal consistency, test-retest reliability, measurement error, and hypothesis testing for construct validity. For statistical analysis, the Intraclass Correlation Coefficient (ICC2,1), Cronbach's α and Smallest Detectable Change (SDC), Pearson's correlation and Confirmatory Factor Analysis (CFA) were used; 2) This is a prospective longitudinal case-control study to verify the test-retest reliability and error measurement of sensorimotor tests. The sample consisted of 203 participants of both sexes, 102 participants with CLD and 101 controls. Test-retest reliability, measurement error and discriminative validity were performed. For statistical analysis, the Intraclass Correlation Coefficient (ICC2,1 - ICC<0.5 = low reliability, 0.5<ICC<0.75 indicates moderate reliability and 0.75<ICC<0.90 = good reliability and ICC>0.90 = excellent reliability), kappa coefficient, SDC and multivariate analysis of covariance (MANCOVA) were used. Results: 1) The structural validity confirmed the unidimensionality of the FreBAQ-Br. The internal consistency was adequate (α = 0,84-0,85). The reliability of the FreBAQ-Br was adequate (ICC2,1 = 0,81-0,82). The measurement error was 3,33-3,23. The hypothesis test confirmed 94,11% of the a priori hypotheses. 2) The TPD showed moderate reliability for DLC and controls, the SDC was 8-10 mm for DLC and 9 mm for controls. The LRJT in DLC demonstrated good and moderate reliability in the accuracy of the right side (LD) and left side (LS), respectively, with SDC ranging from 8,77% to 22%. For the response time, the reliability was moderate in LD, LS and in the error time. In the error time of the column in the context mode, it was considered low in LS. In asymptomatic individuals, the accuracy of LD and LE showed good and moderate reliability, respectively, with SDC between 7,16% and 17,73%. However, for the column (context mode - LE), it showed low reliability. For response time, reliability in LD and LE was moderate, except for the time to hit the column (context) on both sides, which obtained good reliability. BID showed moderate reliability in DLC and excellent in controls for self-assessment. Furthermore, the tests demonstrated discriminative capacity. Conclusion: The FreBAQ-Br showed good measurement properties. The sensorimotor tests generally show adequate reliability and have discriminative capacity. Thus, according to the results, the FreBAQ, TDP, LRJT and BID instruments can be used in clinical practice and research.
Measurement properties of instruments for assessing sensorimotor alterations in individuals with chronic low back pain and asymptomatic individuals
Keywords: Dor lombar; Propriedades de medida; Córtex somatossensorial; Fisioterapia; Low back pain; Validation study; Somatosensory cortex; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL